Growing characteristics of apple cultivars and canopies - Csihon, Á.; Holb, I. J.; Gonda, I. (International Journal of Horticultural Science, 2015)
In our study we aimed to evaluate the growing characteristics of new prospective apple cultivars and their canopies. The following parameters were measured: I) thickness of the trunk and the central leader, II) ratio of the trunk thickness and the basic branches (Zahn indexes), III) number of the branches of the central leader, and iv) thickness of the branches of the central leader. The main branches of the trunk and the central leader tend to over thickening in the case of cvs ‘Red Idared’, ‘Wilton’s Red Jonaprince’ and ‘Jeromine’. The density of the branches of certain parts of the canopy was too low for cvs ‘Crimson Crisp’, ‘Wilton’s Red Jonaprince’, ‘Fuji September Wonder’ and ‘Red Idared’. The density of the branches of certain parts of the canopy was too high for cvs ‘Gala Venus Fengal’, ‘Wilton’s Red Jonaprince’ and ‘Red Cap Valtod’. Relationship was found between the tapering dynamics of the central axis and the thickness of the main branches, which was stronger in super spindle canopies than in slender spindle crown forms.